2022
DOI: 10.1021/acs.iecr.1c04419
|View full text |Cite
|
Sign up to set email alerts
|

Covalently Immobilized Nickel Nanoparticles Reinforce Augmentation of Mass Transfer in Millichannels for Two-Phase Flow Systems

Abstract: Process intensification in millichannels is gaining momentum due to its wider applications and several operational advantages compared to microreactors. Nanoparticle-immobilized millimeter-sized channels have the potential to address the further enhancement of mass transfer by effective micromixing of a solute in the desired solvent. The present work provides a comprehensive study on the flow behavior and mass-transfer characteristics of nanoparticle-assisted systems. Toluene−acetic acid and water are chosen a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Metallic Ag, Pt, Au, Ni, Cu, Pd Covalent immobilization ➢Covalently immobilized nanoparticle helps to prevent leaching of nanocatalyst in immobilized reaction systems. 178 ➢Improve stability, and oxidation resistance of nanoparticles.…”
Section: Nanoparticle Immobilizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Metallic Ag, Pt, Au, Ni, Cu, Pd Covalent immobilization ➢Covalently immobilized nanoparticle helps to prevent leaching of nanocatalyst in immobilized reaction systems. 178 ➢Improve stability, and oxidation resistance of nanoparticles.…”
Section: Nanoparticle Immobilizationmentioning
confidence: 99%
“…Reduces nanoparticle leaching tendency and reduces separation cost. 178 2. Increase catalytic efficacy and separability of microchannels.…”
Section: Functionalized Nanoparticles For Biomedical Applications And...mentioning
confidence: 99%
See 1 more Smart Citation
“…Nanoparticles (NPs) play an essential role in improving the kinetics of gas hydrates, and the evolution of nanotechnology demonstrates its utility in biofuels, , CO 2 capture, pharmaceuticals, and enhancing the mass transfer and chemical kinetics of processes. , Said et al have reported that nanoparticles with higher interfacial surface area and tuning surface parameters positively affect gas uptake during CO 2 hydrate formation. They observed that SiO 2 NPs have a more pronounced effect on gas consumption than Al 2 O 3 and Cu nanoparticles .…”
Section: Co2 Sequestration In Hydratementioning
confidence: 99%
“…As previously stated, DAC is a way of directly capturing CO 2 from the atmosphere to reduce global CO 2 concentrations, making it a typical negative emission technology. Nanomaterials have a high specific surface area, excellent chemical and thermal stability, and immense surface functionality. This makes them a suitable material for carbon capture, which considerably enhances the adsorption capacity in the context of DAC development. , Furthermore, because of their tiny size, nanoparticles have high mobility in solution, allowing small concentrations of nanomaterials to swiftly spread in volume . When investigated with various organic linkages using SALE (solvent-aided ligand exchange), ZIF-8 (zeolitic imidazole framework-8) nanoparticles, which is a subclass of metal–organic frameworks, show great potential for CO 2 adsorption.…”
Section: Emergence Of Nanomaterials To Aid Sorbentsmentioning
confidence: 99%